2023
DOI: 10.1002/casp.2724
|View full text |Cite
|
Sign up to set email alerts
|

Being cut off from social identity resources has shaped loneliness during the coronavirus pandemic: A longitudinal interview study with medically vulnerable older adults from the United Kingdom

Abstract: Loneliness is a pernicious problem in older adulthood, associated with physical decline and isolation from valued social groups. However, the long‐term evolving experiences of ageing, identity and loneliness have yet to be elucidated. We use a Qualitative Longitudinal Research interview approach with nine vulnerable older adults (Agemean = 79.4 years), in which five participants were interviewed twice between 2019 and 2020, and four participants were interviewed at three‐time points from 2019 to 2021. This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Within a shorter timeframe, the three‐wave survey by Du, Livingstone, and Adlam (2023) teases apart the relationship between pre‐COVID‐19 multiple group memberships and post‐lockdown mental health through the emergence of mediating factors, including ‘felt understanding’, during lockdown. Similarly, Harkin et al (2023) use longitudinal interviews to gain insights into how the lived experience of COVID‐19 among medically vulnerable older adults evolved along with the shifting government messaging, which served to undermine their positive ageing identities and left them facing a future of uncertainty.…”
Section: The Special Issuementioning
confidence: 99%
See 2 more Smart Citations
“…Within a shorter timeframe, the three‐wave survey by Du, Livingstone, and Adlam (2023) teases apart the relationship between pre‐COVID‐19 multiple group memberships and post‐lockdown mental health through the emergence of mediating factors, including ‘felt understanding’, during lockdown. Similarly, Harkin et al (2023) use longitudinal interviews to gain insights into how the lived experience of COVID‐19 among medically vulnerable older adults evolved along with the shifting government messaging, which served to undermine their positive ageing identities and left them facing a future of uncertainty.…”
Section: The Special Issuementioning
confidence: 99%
“…A second theoretical contribution comes from the study of group identities during crisis, which highlights the dual role of group memberships as vulnerabilities and/or sources of resilience. While Donaldson, Cruwys, Dawel, and Chen's (2024) longitudinal study showed that multiple group memberships provided psychological resilience to social anxiety during and after COVID‐19, Harkin et al's (2023) qualitative research on older adults with medical conditions highlighted the unique identity‐related vulnerabilities of this group. For these older adults, government messaging confirmed negative stereotypes of helplessness and dependency, regardless of their physical condition and deprived them of the active prosocial roles (and associated group memberships) within their local communities that gave many of them a sense of meaning and purpose in retirement.…”
Section: The Special Issuementioning
confidence: 99%
See 1 more Smart Citation